Pengaruh Kadar Garam dan Jenis Kemasan terhadap Mutu Terasi Rebon (Life Science, 2022)
Terasi is a fermented shrimp product with the addition of salt. Fermentation with salt causes protein degradation into amino acids. One of the amino acids, namely glutamic acid, is the producer of the distinctive taste of shrimp terasi. Salt concentration and type of packaging are important factors in the process of making shrimp terasi. This study aims to analyze the effect of salt content and packaging on the quality of rebon (Acetes sp.). shrimp terasi. This research is an experimental study using 2 types of treatment with 3 repetitions. The first treatment was salt concentration, namely 5%, 10%, and 15%. The second treatment was the type of packaging (banana leaves and aluminum foil). Parameters tested include organoleptic, protein content, water content, and microbial content. The shrimp terasi made with different levels of salt and packaging were all acceptable to the panelists, with a value of 7.2-8.6. The results showed that the organoleptic value of shrimp terasi ranged from 7.65-8.32, meaning that the product was acceptable to consumers. The protein contained in shrimp terasi with a salt content of 10% in banana leaf packaging is 16.40%, while with a salt content of 10% and 15% in aluminum foil packaging are 15.75% and 16.86%, according to SNI standards. that is at least 15%. The water content of the shrimp terasi ranges from 32-45%. The number of Escherichia coli colonies in all shrimp terasi samples ranged from 2.23-7.30 Log CFU/g. It was concluded that the best quality of rebon shrimp terasi was shrimp paste made with 10% salt content and packed with banana leaves, with an organoleptic value of 8.6, protein content of 16.4%, water content of 32% and E. coli contamination 2.23 Log CFU/g. Terasi merupakan produk fermentasi udang dengan penambahan garam. Fermentasi dengan garam menyebabkan degradasi protein menjadi asam amino. Salah satu asam amino yaitu asam glutamat, sebagai penghasil cita rasa khas terasi. Konsentrasi garam dan jenis kemasan merupakan faktor penting pada proses pembuatan terasi. Penelitian ini bertujuan untuk menganalisis pengaruh kadar garam dan jenis kemasan terhadap mutu terasi rebon (Acetes sp.). Penelitian ini merupakan penelitian ekperimental menggunakan 2 jenis perlakuan dengan 3 kali pengulangan. Perlakuan pertama adalah konsentrasi garam yaitu 5%, 10%, dan 15%. Perlakuan kedua adalah jenis kemasan (daun pisang dan aluminium foil). Parameter yang diuji meliputi organoleptik, kadar protein, kadar air, dan kandungan mikroba. Terasi yang dibuat dengan perbedaan kadar garam dan kemasan semuanya dapat diterima oleh panelis, dengan nilai 7,2-8,6. Hasil penelitian menunjukkan bahwa nilai organoleptik terasi berkisar 7,65-8,32 artinya produk tersebut dapat diterima konsumen. Protein yang terdapat dalam terasi dengan kadar garam 10% kemasan daun pisang sebesar 16,40%, sementara dengan kadar garam 10% dan 15% pada kemasan aluminium foil berturut-turut sebesar 15,75% dan 16,86 %, sesuai dengan standar SNI yaitu minimal 15%. Kadar air terasi berkisar antara 32-45%. Jumlah koloni Esherichia coli pada semua sampel terasi berkisar 2,23-7,30 Log CFU/g. Disimpulkan bahwa kualitas terasi rebon yang paling baik adalah terasi yang dibuat dengan kadar garam 10% dan dikemas dengan daun pisang, dengan nilai organoleptic 8,6, kadar protein 16,4%, kadar air 32% dan cemaran E. coli 2,23 Log CFU/g. Perlu ditambahkan kebaruan informasi yang diperoleh dari penelitian ini. Keywords: rebon shrimp terasi; salt; banana leaves; aluminium foil terasi rebon; garam, daun pisang; aluminium foil